Invoking Lakshmi : the goddess of wealth in song and ceremony - Rhodes, Constantina Eleni, 1954- (Book collections on Project MUSE., 2010)
Beautiful, beloved Lakshmi is the Hindu goddess of wealth, happiness, and abundant good fortune. This fascinating book is the first comprehensive guide to this celebrated goddess, her worship, and the deeper spiritual domain of prosperity she reveals. Constantina Rhodes presents over five hundred elegantly translated Sanskrit verses, including devotional songs, mantras, visualizations, and ceremonial instructions that devotees use to invoke Lakshmi.